2018
DOI: 10.1021/acssuschemeng.8b01543
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Trace Ethylene at 0 °C over Platinum Nanoparticles Supported on Silica

Abstract: Oxidation of trace ethylene (50 ppm) at 0 °C was systematically studied using Pt nanoparticles supported on mesoporous silica (SBA-15) in a fixed-bed flow reactor. The SBA-15 supported Pt catalyst (1.8 wt % Pt loading) exhibited an ethylene conversion higher than 99% at the initial stage, which gradually began to decrease at 90 min and reached 33% within 240 min. The CO2 yield was lower than the corresponding ethylene conversion before the steady state was reached. This was due to the formation of intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…17,18 TEM measurement of Pt/A380(800) in this study shows that Pt nanoparticles in size of 5.5 nm are highly dispersed on A380(800) surface (FiguresS1(C) and (D)). Structural parameters and catalytic activity for silica-supported Pt catalysts.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…17,18 TEM measurement of Pt/A380(800) in this study shows that Pt nanoparticles in size of 5.5 nm are highly dispersed on A380(800) surface (FiguresS1(C) and (D)). Structural parameters and catalytic activity for silica-supported Pt catalysts.…”
mentioning
confidence: 53%
“…The difference between conversion and yield will disappear when prolonging the reaction time, which means the reaction reaches actual steady-state. 17 However, extremely low ethylene concentration requires a high SV and a long reaction time to assess the steady-state activity.…”
Section: Structure and Catalysis Ofmentioning
confidence: 99%
“…The results revealed that the ethylene conversion capacity could be recovered by removing the water molecules accumulated on the Pt surfaces. According to the previous study, the ethylene decomposition over the catalyst occurs via the HCHO intermediate state. The reaction starts with the absorption of ethylene molecules on the Pt species.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 However, the deactivation due to sintering at high reaction temperature (400-600 C) and wet (H 2 O) feeds remains a challenge. 9,10 Attempts have been made to resolve catalyst deactivation by adding Pt to Pd-based monometallic catalysts. [11][12][13][14] Nevertheless, the inuence of Pt on the improvement of bimetallic Pd-Pt catalysts is inconclusive.…”
Section: Introductionmentioning
confidence: 99%